Metatese: trajetos de ressignificação de marcas (auto)biográficas de um pesquisador em formação - Santos, Fabiano Pereira dos (2025)
This thesis, presented as a metathesis, methodologically reflects on its own process of development, engaging reflexively in the search for meaning in my doctoral journey in the field of Education. Unlike the structure of traditional academic theses, the text is not composed of an introduction and chapters but rather four horizons and anchoring points that interconnect, replacing conventional sections and forming a whole that represents the completeness of my doctoral process. Instead of a central hypothesis, I defined as my investigative focus the objective, subjective (foundational experiences), and procedural marks that constitute my formative process and underpin each anchoring point. The problem that guided the constitution of the metathesis and, reflexively, my trajectory as a researcher can be summarized in the following question: What marks have constituted my doctoral formation in the field of Education? This question implicitly entails not only an attempt to locate these marks but also to understand them. Therefore, I turned to cultural studies, drawing from Stuart Hall and Anthony Giddens in the Eastern Horizon, assuming the specific objective of demonstrating the viability of the metathesis as a formative device. The autobiographical perspective inspired by Marie-Christine Josso, in dialogue with the studies in/of/with everyday life led by Nilda Alves, and the multireferential approach advocated by Jacques Ardoino reinforced the importance of temporally and spatially situating the marks to assign them meaning throughout my formation. In this context, I embraced the writing of my life story (Western Horizon) as a specific objective aimed at providing significant support for the marks and the reflection on the historicity of the metathesis itself (Northern Horizon). This movement was essential to constitute a completeness of meaning in which the marks could be signified. The construction of the metathesis as a form of narration, in which the text incorporates characteristics of a poetic research environment, allowed me to project myself as an author through the figure of the narrator who guides an investigative journey in search of understanding how the researched character—the researcher—was formed throughout my trajectory. To develop this comprehensive process in the Southern Horizon, I articulated theoretical resources from Paul Ricoeur’s hermeneutics and Edgar Morin’s complexity theory, along with Walter Benjamin’s narrative theory and cultural studies (already mentioned), which enabled me to interpret the marks identified throughout the thesis as biographical marks, whose constant resignification is associated with the fragmented and fluid identity in postmodernity. I understood that these biographical marks, narratively mediated, became integrated into my life story dynamically, adjusting to different self-profiles in various social situations. Based on this understanding, at the conclusion of the metathesis, I proposed a simplified formative device for the resignification of biographical marks, advancing the reflections developed throughout my formative journey.